Effect of an injury prevention program on muscle injuries in elite professional soccer - Owen, A. L.; Wong, D. P.; Dellal, A.; Paul, D. J.; Orhant, E.; Collie, S. (The Journal of Strength and Conditioning Research, 2013)
Due to the continual physical, physiological, and psychological demands of elite level soccer increasing the incidence and risk of injuries, preventative training programs have become a common feature of soccer players training schedule. The aim of the current investigation was to examine the effectiveness of a structured injury prevention program on the number of muscle injuries and the total number of injuries within elite professional soccer. The present study was conducted over 2 consecutive seasons, of which the first (2008-2009) being the intervention season and the second the control season (2009-2010). In total, 26 and 23 elite male professional soccer players competing within the Scottish Premier League and European competition participated. The training program was performed twice weekly for the entirety of the season (58 prevention sessions). The results revealed an increase in the total number of injuries within the intervention season (88 vs. 72); however, this was largely due to the greater number of contusion injuries sustained within the intervention season (n = 44) when compared with control season (n = 23). Significantly less muscle injuries were observed during the intervention season (moderate effect), and this occurred concomitant with a bigger squad size (large effect, p < 0.001). The findings from this study identify that a multicomponent injury prevention-training program may be appropriate for reducing the number of muscle injuries during a season but may not be adequate to reduce all other injuries.